PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BINA GUNA KIMIA - Kintavini Aribudi Nastiti, 13.05.51.0123 (Students Journal of Economic and Management, 2017)
This study analyzed the influence of leadership, motivation, and the work diciplene to employees performance of PT Bina Guna Kimia. Sampling technique in this research were 79 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing questionnaires in order information. The research objective formulated to determine the effect of leadership, mottivation and the work diciplene to employees performance of PT Bina Guna Kimia.Data were analyzed using factor analysis to test the validity of the question items, cronbach alpha formula to test the reliability of each independent variable in the regression analysis test. The results of the research are: 1) leadership positive and significan effect on employee performance 2) motivation not positive and not significan effect on employee performance 3) the working diciplene has positive and not significan influence on employee performance. Keywords : leadership, motivation, working diciplene and performance.